Tragedi lumpur lapindo di Sidoarjo - Andriani, Nadia Rizki (Maliki Interdisciplinary Journal, 2024)
Lapindo mud is a geological phenomenon that occurs in East Java Province, Indonesia. Sludge itself is the result of a mixture of clay, nutrients and particles that form sediments. This sludge is not only formed due to excess water content in the soil, but is also triggered by magma and hydrothermal intrusion, creating a recision and increasing the pressure below the soil surface. This mud burst first occurred in 2006 which was triggered by the Brantas Block gas exploration drilling by PT Lapindo Brantas and its impact is still felt today. Geological research confirms that errors in drilling by PT Lapindo are the root of Lapindo's mud problems.